The role of activated RET in papillary tumour morphogenesis - Flavin, Richard (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2011)
RET/PTC rearrangements are initiating events in the development of a significant proportion of papillary thyroid carcinomas. Activated RET/PTC mutations are thought to be restricted to thyroid disease, but in this study we propose that these events maybe features of papillary morphology. 57 non-thyroid papillary tumours were examined for RET/PTC rearrangements using interphase FISH, Taqman™ RT-PCR and immunohistochemistry. 20% (3/15) of primary peritoneal carcinoma had detectable RET/PTC] rearrangements by all three methodologies. A further case of similar histotype had an alternate RET/PTC rearrangement. No RET/PTC1 rearrangements were detected in the remaining tumour cohort. Our results indicate that RET/PTC rearrangements occur in a small subset of non-thyroid papillary tumours. These rearrangements may not be directly implicated in tumour growth; rather representing ‘passenger’ mutations reflecting RET instability in secondary tumour subclones.
Keywords: Histopathology and Morbid Anatomy, M.D.; M.D. Trinity College Dublin